Zircon U-Pb geochronology of the Chinese continental crust: a preliminary analysis of the Elsevier science database. Issue 1 (2nd January 2019) - Wu, Yujing; Fang, Xianjun; Liao, Sisi; Xue, Lizhi; Chen, Zhe; Yang, Jiangnan; Lu, Yamin; Ling, Kun; Hu, Shengyi; Kong, Shuyuan; Xiong, Yiwei; Li, Huacheng; et al.
ABSTRACT: The amount of zircon U-Pb geochronological data for China has grown rapidly in recent years. Nearly 410, 000 items of zircon U-Pb geochronological data, representing more than 7, 000 relevant articles in the Elsevier Science Database, have been collected to a database in this research. Statistics on the ages and absolute errors of these collated data, yielded smallest standard errors for ( 206 Pb/ 238 U), ( 207 Pb/ 235 U), and ( 207 Pb/ 206 Pb) ages within respective time intervals of < 1388.96 Ma, 1388.96–3282.52 Ma, and > 3282.52 Ma. The ages and their absolute errors were determined using three main geochronology methods, based on laser ablation inductively coupled mass spectrometer (LA-ICP-MS), sensitive high-resolution ion microprobe (SHRIMP), and secondary ion mass spectrometer (SIMS) measurements. We compared the influence of these different methods on errors for each age interval. In addition, using a Gaussian model of multi-peak fitting of zircon U-Pb age frequencies, we identified seven growth peaks in zircons from the Chinese continental crust, which are 48.60 Ma, 131.49 Ma, 249.91 Ma, 444.27 Ma, 835.95 Ma, 1860.65 Ma, and 2505.54 Ma. It is clear that there are correspondences between these ages and various geological events, namely, the Wutai movement, Lvliang movement, Jinning movement, Caledonian movement, Indo-China movement, Yanshan movement, and Himalayaorogeny movement, respectively. The time and spatial distributions of these zircons correspond to distinct geological events on the Chinese continent, reflecting its crustal evolution.